Preliminary Study On The Development of Project-Based Learning Module to Improve Students' Mathematical Problem Solving Ability - Difinubun, Fajria Ahmad; Makmuri, Makmuri; Hidayat, Flavia Aurelia (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
Mathematical problem solving skills are important for high school students, but are still low. The contributing factor is that learning does not emphasize problem solving and involve students. Teaching materials are not suitable with students' characteristics. Teacher skills in developing problem solving-based learning are still low. This study aims to develop a learning module based on Project Based Learning (PBL) to improve the mathematical problem solving skills of high school students in grade XI on the sequence nd series topic. Testing the effectiveness of the PBL module on improving students' mathematical problem solving skills. This research uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model to develop the PBL module. In the analysis stage, data were collected through observation, questionnaires, interviews, and tests to find out students' problems in learning the material of sequence nd series. The test results of students' mathematical problem solving skills showed that 91% of students had low mathematical problem solving skills. At the design stage, the PBL module was designed by considering the results of the student needs analysis and the characteristics of the sequence nd series material. This module contains various learning activities that involve students actively in solving problems related to everyday life.In the next stage, the PBL module that has been designed will be implemented in the experimental class and tested for its effectiveness in improving students math problem solving ability.